Effects of normal and through-thickness shear stresses on the forming limit curves of AA3104-H19 using advanced yield criteria. (March 2018) - Nasiri, S.M. Mirfalah; Basti, A.; Hashemi, R.; Darvizeh, A.
Highlights: Generalized forming limit diagram (GFLD) for AA3104-H19 alloy is investigated by employing three advanced anisotropic yield criteria, including Yld96, Yld2004 and Yld2011. The M–K model is modified by considering the normal and through-thickness shear (TTS) stresses. The GFLD analysis of AA3104-H19 indicates that the predicted limit strain by implementing of Yld96 yield criterion is the largest. The normal stress has more considerable effect than of out of plane shear stress condition to increase the formability of sheet metal. Abstract: In the present study, the effects of normal and through-thickness shear (TTS) stresses are simultaneously considered to predict the generalized forming limit diagram (GFLD) of AA3104-H19 using Yld96 [1], Yld2004 [2] and Yld2011 [3] anisotropic yield criteria. For this purpose, considering the general stress state, including the normal and through-thickness shear stresses, the modified Marciniak–Kuczynski (M–K) model is employed. The Newton–Raphson numerical method is applied to solve the nonlinear equations set, and then the forming limit diagram (FLD) and forming limit stress diagrams (FLSD) are computed. First, the forming limit curves are presented by considering the through-thickness shear stress, and then the generalized forming limit curves are presented by applying the normal and through-thickness shear stresses simultaneously. The results show that the through-thickness shear stress has positive sensitivity on the limit strains. Also, the normal stress is more efficient than the through-thickness shear stress on the formability of the plate. Comparison between the results indicates that the predicted limit strains by the Yld2011 anisotropic yield function are lower than those predicted by Yld96. Graphical abstract: